2020
DOI: 10.1039/c9an01565e
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the presence of biogenic selenium nanoparticles in yeast cells: analytical strategies based on ICP-TQ-MS

Abstract: Complementary analytical strategies based on ICP-TQ-MS were used for the detection and characterization of selenium-containing nanoparticles in selenized yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…In another work, Álvarez-Fernández García et al reported a value of 69 ± 3% for yeast cells using a similar device. 138 …”
Section: Interrogating Single Cells the Development Of Mass Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In another work, Álvarez-Fernández García et al reported a value of 69 ± 3% for yeast cells using a similar device. 138 …”
Section: Interrogating Single Cells the Development Of Mass Cytometrymentioning
confidence: 99%
“…while for 30 nm Au NPs they reported a TE of 70%. In another work, Álvarez-Fernández García et al reported a value of 69 ± 3 % for yeast cells using a similar device 138. Another direct injection device with a custom-made concentric nebulizer and an almost total consumption spray chamber was proposed by Wei et al,139 providing a TE value of 42.1 ± 7.2 %, as evaluated with 30 nm Au NPs.…”
mentioning
confidence: 96%
“…This was due to the larger sizes of each cell (~5 μm, Figure 3) compared to the silica nanoparticles (200 nm). Nanosized particle material can be effectively introduced into ICP-MS. [8] Even for micrometer-sized cell samples, high transport efficiency was achieved more than 70 % when a concentric nebulizer with a capillary tube was used. [6,9] In this study, a typical concentric nebulizer was used for nebulization.…”
Section: Analytical Performance Of the Sc-icp-ms Systemmentioning
confidence: 99%
“…Álvarez‐Fernández García et al. then used SC‐ICP‐MS for the detection of Se in selenium‐enriched yeast [8] . For mammalian cell characterization, Cao et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation